Adjusting the natural stiffness of a pneumatic powered exoskeleton designed as a virtual reality haptic device. (8th November 2017) - Chakarov, Dimitar; Veneva, Ivanka; Tsveov, Mihail; Zlatanov, Evgeni
This study describes the natural stiffness of a pneumatic powered exoskeleton arm, designed as a haptic device in virtual reality applications. It is important for the haptic device to provide a natural, safe, and comfortable physical mutual human–robot interaction as well as realism for the haptic feedback. To meet these requirements, an exoskeleton possessing an actuation system based on pneumatic artificial muscles and feedforward impedance control is presented. A natural stiffness controller is included to passively adjust the desired stiffness of the exoskeleton. The parameters of the actuation system that determine the natural exoskeleton stiffness are analyzed. A scheme is constructed for joint torque control and end-effector stiffness adjustment under the antagonistic action of the pairs of pneumatic actuators. An optimization-based approach is created for specifying the parameters determining the natural stiffness of the exoskeleton arm. Computer simulations are conducted for a preliminary assessment of options for adjusting the Cartesian stiffness. Additional experiments are performed for specifying the object stiffness according to the scenario of virtual gymnastics.